Makna Isbat Dalam Manuskrip Syattariyah Merbabu Sebagai Representasi Pendidikan Agama Seorang Individu - Argo Prasetyo, Dandung Adityo (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
This research aims to examine the education of religiosity in the Syattariyah Merbabu manuscript through isbat (unen-unen), which is a classical manuscript representing Sufi teachings in the context of Nusantara Islam. This research is a qualitative descriptive study using a grammatical hermeneutic approach. The data for this research is the text of the Syattariyah Merbabu manuscript. This research will collect all the educational values found within the Syattariyah Merbabu manuscript by analyzing the text translation in detail. The results of this study found that the educational structure in the manuscript includes four main stages: sharia, tarekat, hakikat, and makrifat. The educational process is not only normative but also transformative through remembrance (dzikir), meditation (samadi), and spiritual guidance. The spiritual ethics taught in the texts through self-discipline, control of desires, and the purification of speech and thoughts hold strong character education values, in line with the spirit of integrative Islamic education. The relevance of these teachings to contemporary Islamic education shows that the local Sufi heritage can be adapted to shape character and spiritual awareness in the modern educational world.